Tertiary granitic rocks along the Southern margin of the Pannonian basin - Knežević Vera (Acta mineralogica-petrographica, 1994)
The Oligocene-Miocene granitic magmatism of the Bukulja-Cer-Motajica (BCM) belt developed as follows: - from about 30 Ma until 25 Ma ago I-type magmas gave in the BCM belt the hornblende bearing granodiorites of Brajkovac and Bukulja, the tonalites of Bogatic and the deep seated facies of the quartz monzonites of Cer as the first and the biotite granites of Bukulja and the dyke rocks of Brajkovac as the final products. - around 20 Ma ago strng heating along the BCM belt induced mobilization to melting of older granitic rocks. The reomorphic intrusion of mobilized/initially melted rock masses gave the quartz monzonite of Cer and from the intruded highly melted masses originated the biotite graniodiorite of Stra2anica. - about 18 Ma ago S-type magmas were intruded and gave muscovite bearing granites of Bukulja, Cer and Brajkovac (?). • - the magmatism of the first two phases is widespread in all the Central Balkan peninsula, the youngest S-granitic phase is restricted to the BCM belt only because of specific geotectonic conditions along the southern margin of the Pannonian basin.